IDENTIFIKASI LABU NUSANTARA (Cucurbita moschene Dutchene) SEBAGAI DIVERSIFIKASI PANGAN SUMBER KARBOHIDRAT - Reza Prakoso Dwi Julianto; Astri Sumiati (Jurnal Ilmiah Hijau Cendekia, 2017)
Population growth and shrinkage of productive agricultural land led to the availability of rice as a staple food of the population became unbalanced. Efforts to reduce dependence on rice, the food diversification efforts Alternative High carbohydrate should be done so that the robustness, security and sovereignty panganakan remains guaranteed. Plant squash (pumpkin) is one of the plants that have a high carbohydrate content and has many kinds, so this will make it easier in assembly activities yielding varieties. This study aims to collect many different varieties of pumpkin archipelago as starting materials in the assembly of high yielding varieties of activities, and to investigate and identify the character of vegetative and agronomic characters varieties of pumpkin archipelago. Penelitiandilaksanakan in Randuagung village, Lumajang with altitude of 112 meters above sea level above sea level (asl). Materials used in this study a local pumpkin seeds and pumpkin Lumajang local poor. These results indicate that the ratio of male flowers and female flowers on both varieties of local pumpkin shows the number of male flowers are more than the amount of beta-carotene betina.Kadar interest in Lumajang local pumpkin lower than the local pumpkin unfortunate it is seen from the color of pumpkin faded yellow more yellow and less sense to disease manis.Ketahanan both local pumpkin varieties showed criteria tahan.Umur local male flowers of pumpkin unfortunate faster than local pumpkin Lumajang, but the age of the female flower local pumpkin Lumajang faster than local yellow squash malang.Warna local pumpkins are relatively similar; Lumajang brown, while the local varieties of pumpkin unfortunate there is a difference that is brown and green